On the contribution of synoptic transients to the mean atmospheric state in the Gulf Stream region - Parfitt,R; Czaja,A (Quarterly Journal of the Royal Meteorological Society, 2015)
A new decomposition of the time mean sea level pressure, precipitation, meridional velocity (v) and pressure vertical velocity (ω) is applied to ERA-Interim reanalysis data over the North Atlantic ocean for the December-February 1979–2011 time period. The decomposition suggests that the atmosphere over the Gulf Stream is dominated by a continuous series of synoptic systems, or baroclinic waves, propagating across the region. The time mean value of precipitation, meridional velocity and ω (the latter being taken as a proxy for upward and downward motion) is accordingly set by the propagating waves. The result is particularly striking for ω (v) considering that ascent and descent (poleward and equatorward flow) could reasonably be expected to cancel out in such a series of waves.These results shed a new light on analyses of the storm track heat budget in which the residual between diabatic heating and “transient” eddy heat fluxes (singled out through band pass time filtering or spatial Fourier analysis) is interpreted as a Rossby wave source. This interpretation is questioned because, as a consequence of the filtering used, these studies prevent any direct contribution of the “transients” to the time mean ω or meridional velocity, attributing entirely both fields to the circulation associated with the thermally forced Rossby wave. The fact that “transients” directly contribute to the observed time mean ω over the Gulf Stream might also explain the discrepancy between the observed and predicted response of the vertical motion field to heating in midlatitudes.